1990
DOI: 10.1038/bjc.1990.127
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between altered intracellular pH and multidrug resistance in mammalian cells

Abstract: SummaryThe intracellular pH of a number of multidrug resistant cell lines was compared with that of their parental lines using the fluorescent probe bis-carboxyethylcarboxyfluorescein. In four different cases, cells having 5-fold resistance or more exhibited an intracellular pH which was 0.10-0.17 units higher than that of the parental cell line. A CHO cell line, AB,, and its 180-fold resistant counterpart, CHRC5, were further investigated with regard to the role of Na+/H+ antiport. The Na+/H+ antiport activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 16 publications
3
36
1
Order By: Relevance
“…The results of this work are partly in agreement with previous observations, showing that MDR cells exhibit a higher NHE activity. 28,29 Differently from Boscoboinik and colleagues, 28 who did not observe a reversal of MDR with amiloride, in our experiments EIPA (at the concentration able to inhibit NHE activity in the same cells) did cause an increase of the chemotherapeutic accumulation. This discrepancy could be accounted for by the different cells and inhibitor used: indeed, amiloride is a less potent and less specific inhibitor of NHE than EIPA.…”
Section: Discussioncontrasting
confidence: 41%
“…The results of this work are partly in agreement with previous observations, showing that MDR cells exhibit a higher NHE activity. 28,29 Differently from Boscoboinik and colleagues, 28 who did not observe a reversal of MDR with amiloride, in our experiments EIPA (at the concentration able to inhibit NHE activity in the same cells) did cause an increase of the chemotherapeutic accumulation. This discrepancy could be accounted for by the different cells and inhibitor used: indeed, amiloride is a less potent and less specific inhibitor of NHE than EIPA.…”
Section: Discussioncontrasting
confidence: 41%
“…It has been suggested that sensitisers increase drug accumulation by competing with cytotoxic drugs for sites on the P-glycoprotein efflux pump (Horio et al, 1988). However, one sensitiser, cyclosporin A, has been shown to reverse acquired MDR in some cell lines but not in DC3F/ADX cells, despite the fact that these cells overexpress P-glycoprotein (Boscoboinik et al, 1990). The mechanism of intrinsic MDR is even less well understood.…”
Section: Resultsmentioning
confidence: 94%
“…In this context, our observation that the intrinsic and acquired MDR phenotypes differ with regard to their reversal by amiloride analogs points to some subtle differences in the resistance mechanism. It should however, be mentioned that acquired MDR cell lines which overexpress P-glycoprotein are also known to differ in their reversal characteristics by cyclosporin A (Boscoboinik et al, 1990). The different reversing agents may provide a valuable probe for examining the heterogeneity of the MDR phenotype and for investigating the underlying mechanism(s).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the phenomenon is known as multidrug resistance (MDR). The most well-studied mechanism of multidrug resistance involves the MDR-1 gene product, P-glycoprotein (P-gp), a drug pump which also transports protons (Thiebaut et al, 1990;Boscoboinik et al, 1990). However, P-gp accounts for only 50% of the observed MDR phenotypes (Gottesman and Pastan, 1993).…”
Section: T 1 and T 2 Measurementsmentioning
confidence: 99%